Housing affordability for public servants in Bauchi State, Nigeria - Amamata Larai Zakari, 1978- author; Rosadah Mahamud, supervisor; Fakulti Geoinformasi dan Harta Tanah (2014)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2014